Revised stratigraphy in the eastern Meguma terrane, Nova Scotia, Canada, and variations in whole-rock chemical and Sm–Nd isotopic compositions of the Goldenville and Halifax groups - Barr, Sandra M.; White, Chris E.; Pin, Christian (Atlantic Geoscience, 2022)
As a result of new geological mapping, the Goldenville and Halifax groups in the eastern Meguma terrane have been divided into formations. They have a total stratigraphic thickness of about 7750 m and correspond to only the upper half of the Goldenville Group and lower half of the Halifax Group in the northwestern and southeastern areas of the terrane. The revised stratigraphy combined with compiled and new whole-rock major and trace element and Sm–Nd isotopic analyses enable more detailed documentation of the chemical changes with stratigraphy that were demonstrated in previous studies. Based on chemical compositions, the protolith compositions of the analysed samples range from lithic arenite to wacke to shale. Major and trace element characteristics are consistent with deposition in an active continental margin, basins associated with island arcs, or most likely at a passive continental margin with volcanic rocks in the source area. Chemical compositions show a scattered but overall increasing abundance of lithophile elements such as La and Th with stratigraphic position. Epsilon Nd(t) values become increasingly negative up-section, and depleted mantle model ages become increasingly older. The data are consistent with increased mixing between sediments derived from Mesoproterozoic upper crustal sources and sediments derived from a magmatic arc. These data are consistent with published detrital zircon patterns which show increasing amounts of ca. 2 Ga zircon with decreasing age, and with a source area comprising a Pan-African (800–540 Ma) volcanic arc and/or active margin magmatism and mainly Eburnean crust, most likely in the West African craton.